The legal framework for refugee resettlement to the European Union with lessons from the American model - Prantl, Janine (Schriften zum Migrationsrecht, 2023)
This book elucidates the international and EU legal framework for refugee resettlement to the European Union. Firstly, it provides clarity on the concept of resettlement. Secondly, it identifies the international legal obligations of states applicable to resettlement, and thirdly, it sets out the relevant EU legal bases of competence and limits to the exercise of competence. Finally, the legal dogmatic analysis, as well as a comparison with resettlement practices in the United States, serve as foundation for recommendations for a future EU legal framework.